Design and evaluation of 1, 7-naphthyridones as novel KDM5 inhibitors. Issue 18 (15th September 2016) - Labadie, Sharada S.; Dragovich, Peter S.; Cummings, Richard T.; Deshmukh, Gauri; Gustafson, Amy; Han, Ning; Harmange, Jean-Christophe; Kiefer, James R.; Li, Yue; Liang, Jun; Liederer, Bianca M.; Liu, Yichin; et al.
Graphical abstract: Abstract: Features from a high throughput screening (HTS) hit and a previously reported scaffold were combined to generate 1, 7-naphthyridones as novel KDM5 enzyme inhibitors with nanomolar potencies. These molecules exhibited high selectivity over the related KDM4C and KDM2B isoforms. An X-ray co-crystal structure of a representative molecule bound to KDM5A showed that these inhibitors are competitive with the co-substrate (2-oxoglutarate or 2-OG).